Implementation of MR-linac and proton therapy in two radiotherapy departments in The Netherlands: Recommendations based on lessons learned. (February 2022) - Jacobs, Maria; Kerkmeijer, Linda; de Ruysscher, Dirk; Brunenberg, Ellen; Boersma, Liesbeth; Verheij, Marcel
Abstract: Recently, two new treatment techniques, i.e. proton therapy and MR-linac based radiotherapy (RT), have been introduced in Dutch RT centres with major impact on daily practice. The content and context of these techniques are frequently described in scientific literature while little is reported about the implementation phase. This process is complex due to a variety of aspects, such as the involvement of multiple stakeholders, significant unpredictability in the start-up phase, the impact of the learning curve, standard operating procedures under development, new catchment areas, and extensive training programs. Insight about implementation in daily care is utterly important for clinics that are about to introduce these new technologies in order to prevent that every centre needs to reinvent the wheel. This position paper gives an overview of the implementation of proton therapy and MR-linac based RT in two large academic RT centres in the Netherlands, i.e. Maastro and Radboudumc respectively. With this paper we aim to report our lessons learned, in order to facilitate other RT centres that consider introducing these and other new techniques in their departments.